# How do you solve #4x(x+2)=16x-3# by factoring?

$4x^2 - 2x - 6x + 3 = 0#

(2x -3) * (2x - 1) = 0#

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 4x(x+2) = 16x - 3 by factoring, follow these steps:

- Expand the left side of the equation: ( 4x(x+2) = 4x^2 + 8x ).
- Subtract ( 16x - 3 ) from both sides of the equation to set it equal to zero: ( 4x^2 + 8x - (16x - 3) = 0 ).
- Combine like terms: ( 4x^2 + 8x - 16x + 3 = 0 ) simplifies to ( 4x^2 - 8x + 3 = 0 ).
- Factor the quadratic equation: ( 4x^2 - 8x + 3 = (2x - 1)(2x - 3) = 0 ).
- Set each factor equal to zero and solve for x:
- ( 2x - 1 = 0 ) gives ( x = \frac{1}{2} ).
- ( 2x - 3 = 0 ) gives ( x = \frac{3}{2} ).

So, the solutions to the equation ( 4x(x+2) = 16x - 3 ) by factoring are ( x = \frac{1}{2} ) and ( x = \frac{3}{2} ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7